7x-6x=72+x

Simple and best practice solution for 7x-6x=72+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-6x=72+x equation:


Simplifying
7x + -6x = 72 + x

Combine like terms: 7x + -6x = 1x
1x = 72 + x

Solving
1x = 72 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1x + -1x = 72 + x + -1x

Combine like terms: 1x + -1x = 0
0 = 72 + x + -1x

Combine like terms: x + -1x = 0
0 = 72 + 0
0 = 72

Simplifying
0 = 72

Combine like terms: 0 + -72 = -72
-72 = 72 + -72

Combine like terms: 72 + -72 = 0
-72 = 0

The solution to this equation could not be determined.

See similar equations:

| 10+8z=z-5 | | X^15=23838 | | 9+9n=7n+9 | | 10x+20(43-x)=590 | | 10x+20(x-43)=590 | | x^2-(3k-2)x+(k^2-1)=0 | | x=14*3*4 | | 1.3x+5=-35 | | x=15*3*4 | | =15*3*4 | | 4x-(3y-3x)-8y= | | x+10x+25(35-2x)=407 | | -3x=1/ | | 15x+2y-3+5y-6= | | 4x-1=7+x | | 2xy+3x=0 | | 6x(2x+3)=390 | | 18.84=12*3.14 | | 2x-11=5x+1 | | 0y=-4 | | X+15=x*4 | | 7x-(2x+3)=9(x-1) | | Xa+15=x*4 | | 3x+1=4x+8 | | x+8x=3+x | | Y+y+15=23 | | 15/10x4= | | y=-1X+20 | | f(1)=5x^2+100 | | -.2(1-x)=4(4+.1x) | | f(x)=5x^2+100 | | 28078.82+0.9010x+17491.84+0.8746x+8489.33=0.9563x+19126.34+26237.77+0.8489x+8489.33 |

Equations solver categories